O pensar e o fazer interdisciplinar em filosofia: um itinerário de formação e investigação - Evangelista, Francisco (2011)
This research is introduced in The Research Curriculum and Formation Nucleous and its line of research is the interdisciplinerity. This main subject is to present the itinerary of Formation and investigation of the graduated professional in Philosophy and its intend to emphasize the real pedagogical action as a conductor wire in order to the philosophic education happens inside the school environment and also outside of it and considering the pedagogical practice researcher himself as the investigation subject. The reasons of this intensive researches are around of nowadays needs when the educative and didatic practice in Philosophy happens inside and outside of schools. Another reasons are to analyze the present which is the witness more recent of the past hearing the future and it makes a prospective analyze in order to give validate and firm base to the philosophic work. When we study Philosophy hardy we perceive that it is more easy understand it as social,cultural and historic, benefit; this distinguish it as a progressive real life day by day and conscientiouness of the persons involved in this process, consequently, the contents studied inside and outside of classroom are beneficial to their lives. The methodology that was utilized in this research has reflected that one which is the own researcher personal history. This fact approaches the research to the called ego history or more specifically called auto biographic research. This work researches his personal history, revisiting his formation way and his academic investigation. This text analyze his educator trajectory, so he is same time a study object and he is also an investigation process subject. In this research there are reflection and analyze of his history and his real pedagogical practice and over all as professional of the education